2019
DOI: 10.1093/cercor/bhz306
|View full text |Cite
|
Sign up to set email alerts
|

Absence of TRIM32 Leads to Reduced GABAergic Interneuron Generation and Autism-like Behaviors in Mice via Suppressing mTOR Signaling

Abstract: Mammalian target of rapamycin (mTOR) signaling plays essential roles in brain development. Hyperactive mTOR is an essential pathological mechanism in autism spectrum disorder (ASD). Here, we show that tripartite motif protein 32 (TRIM32), as a maintainer of mTOR activity through promoting the proteasomal degradation of G protein signaling protein 10 (RGS10), regulates the proliferation of medial/lateral ganglionic eminence (M/LGE) progenitors. Deficiency of TRIM32 results in an impaired generation of GABAergic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 59 publications
4
37
0
Order By: Relevance
“…VPA is commonly used as an antiepileptic drug. Clinical studies have shown that exposure to VPA in utero is associated with cognitive deficits, birth defects, and an increased risk of ASD [85] . Clinical evidence shows that there is a link between VPA exposure and both cognitive abnormalities and autism.…”
Section: Vpa Modelsmentioning
confidence: 99%
“…VPA is commonly used as an antiepileptic drug. Clinical studies have shown that exposure to VPA in utero is associated with cognitive deficits, birth defects, and an increased risk of ASD [85] . Clinical evidence shows that there is a link between VPA exposure and both cognitive abnormalities and autism.…”
Section: Vpa Modelsmentioning
confidence: 99%
“…The resulting IgG fraction is further purified by absorption on the caspase 3 peptide (human) corresponding to the uncleaved caspase 3 site sequence (Sigma antibody datasheet). Using immunohistochemical techniques with this antibody, active caspase 3 has been detected in several mammalian species including rat (Benitez, Castro, Patterson, Muñoz, & Seltzere, 2014; Molina et al, 2020) and mouse (Zhu et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…At the opposite side of the pathway, the pivotal kinase mTOR is a sensor of metabolic and nutrient stress regulating many cellular processes, including the repression of autophagy in normal conditions. Amongst the numerous E3 ligases that modulate mTOR signaling, two were investigated for autophagy readout: FBXW11 and TRIM32 maintain the repressive activity of mTOR on autophagy by degrading inhibitors of mTOR, respectively DEPTOR (Duan et al, 2011;Gao et al, 2011;Zhao et al, 2011) and RGS10 (Zhu et al, 2020). Directly under the control of mTOR, TFEB, a pivotal transcriptional regulator of autophagy genes is positively modulated by CHIP, which degrades preferentially its phosphorylated inactive forms and induces autophagy (Sha et al, 2017).…”
Section: Emerging Roles Of E3 Ligases In the Control Of Autophagymentioning
confidence: 99%